Evidence for the Continued Occurrence of Chorioretinopathy in Working Sheep Dogs in New Zealand in 2010 - O'Connell AB; Irving AC; Hughes PL; Cogger N; Jones BR; Hill KE (MDPI (Basel, Switzerland), 2021)
A study in conducted 1987 by Hughes et al., found that 39% of working sheep dogs had multifocal retinitis. One of the identified causes was ocular larval migrans, which were a result of migrating ascarid larvae. Since that paper was published, anthelmintic use in farm dogs has been highly recommended. There has been no follow-up study to determine if fundic lesions are still present. The current study aimed to investigate the prevalence of chorioretinopathy in working sheep dogs in the South-West, Waikato, New Zealand. This was a cross-sectional study of 184 working sheep dogs and 51 owners, undertaken in 2010 with owners sampled from New Zealand's South-West Waikato and Tux North Island Dog Trial Championship. Two-way tables were used to explore the relationship between variables. Significance of association was assessed using a Chi-squared or Fisher exact test as appropriate, with a p-value of <0.05 considered significant. Overall prevalence of chorioretinopathy in the working sheep dogs was 44/184 (24%). A significantly higher prevalence of chorioretinopathy was shown in dogs with increasing age, from 2 years to >8 years (p = 0.0007) and in males (p < 0.0001). This study concluded that lesions of chorioretinopathy are still present in working sheep dogs in New Zealand.
Keywords: chorioretinitis; chorioretinopathy; working farm dogs